STRATEGI PENGEMBANGAN BISNIS INDUTRI KREATIF SKALA KECIL MELALUI PENDEKATAN BUSINESS MODEL CANVAS (STUDI KASUS PADA PLATFORM OTT SINEASMOV) - Faradiba Sabina Erdian (POLITEKNIK LP3I JAKARTA, 2024)
This research investigates small-scale creative industry business development strategies, particularly focusing on the OTT platform SineasMov. It observes the growth of the independent film industry in Indonesia and identifies challenges in distributing independent films and the lack of income for independent filmmakers. PT. Sineas Kreatif Indonesia innovates by creating the OTT Platform named SineasMov as a solution to these issues. SineasMov offers TVOD and AVOD services while focusing on networking and events. Through the Business Model Canvas (BMC) analysis, this study clarifies the key elements in SineasMov's business model, highlighting the need for the right business concept to support the company's growth. This research remaps the SineasMov BMC to suggest further development strategies, including enhancing customer segmentation, improving value propositions, diversifying revenue streams, optimizing resources, and strategic partnerships. From the SWOT analysis and the Four Action Framework, a new BMC formulation is proposed to strengthen SineasMov's position in the Indonesian independent film industry market. Key words: Independent Film, Business Model Canvas, OTT Platform.